Phosphate use effiency and phosphate transporter activity of selected oil palm genotypes - Tan, Ngai Paing (2012)
High yield and increasing the production of oil palm in Malaysia depends much on application of fertilizers due to oil palm high nutrient demand, uptake and removal. Malaysian soils (mainly Ultisols and Oxisols), are known to be highly weathered, acidic and inherently low in phosphate and have high P fixing capacities, thus making it unavailable for plant use. Quantitative information on P-use efficiency for crop is vital to ensure a better design of P-management,economically and ecologically. As such, adopting plants with better nutrient uptake efficiency nonetheless means a more environmentally friendly and ecological feasible strategy to improve the growth of plant in low phosphorus soil. A study was conducted to evaluate the variability of phosphate uptake among oil palm genotypes at nursery stage. Nine months of observation revealed that the percentages of the phosphate uptake by the oil palm genotypes could be ranked as genotype D = B ≥ C ≥ F ≥ E ≥ I ≥ G = A ≥ H, which ranged from 15% to 45% of phosphate derived from fertilizer (PdfF). Cluster analysis showed that two major clusters can be identified; Genotype B, D, C, E, F as cluster which take up higher rate of P-fertilizer compared to cluster which comprised Genotype A, G, I, H. Use of tracer (32P) in the fertilizer application provided a mean to understand the fate of fertilizer in the plant, i.e. the quantity of fertilizer being taken up by the plants. Such information allows better management of selecting better genotypes and monitoring the fertilizer use efficiency thus reducing fertilizer wastage. Another experiment was conducted to evaluate the variable activity of phosphate transporter among the genotypes under phosphate starvation. In second study, a 27kD peptide in the root was identified as the P transporter activity in the roots of these oil palm genotypes by using probe during phosphate starvation. Phosphate transporters activity among the genotypes can be ranked as genotype A≥ D ≥ B= E ≥ I ≥ H = C = G = F. Cluster analysis grouped cluster genotype A, B, D, E, I with higher phosphate transporters activity compared to cluster genotype C, G, F, H. The presence of phosphate transporters which were detected only during phosphate starvation may suggest the palm is enhancing the phosphate uptake in root to improve the low phosphate level inside the plant. The result on phosphate transporters in this experiment provides some clues that genetic variants may play a role in terms phosphate uptake efficiency among oil palm genotypes.